438 INCIDENT HYPOCHLOREMIA AMONG PATIENTS WITH TAKOTSUBO SYNDROME: SHORT- AND LONG-TERM OUTCOME. RESULTS FROM A MULTICENTER PROSPECTIVE REGISTRY. (15th December 2022) - Cetera, Rosa; Santoro, Francesco; Vitale, Enrica; Ragnatela, Ilaria; Mallardi, Adriana; Leopizzi, Alessandra; Matera, Annalisa; Correale, Michele; Iacoviello, Massimo; Brunetti, Natale Daniele
Abstract: Background: Takotsubo syndrome (TTS) is an acute heart failure syndrome featured by a reversible left ventricular systolic dysfunction with significant rate of in- and out-of-hospital mayor cardiac adverse events (MACE). Aim of the study: To evaluate the possible role of hypochloremia as prognostic marker at short- and long-term follow-up in subjects with TTS. Methods: 305 consecutive patients were enrolled in a multicenter international registry. Clinical, laboratory and echocardiographic evaluations were performed at admission and during hospitalization. Incident hypochloremia (serum chloride level below 97 mEq/l) during hospitalization was recorded. In-hospital MACE, short- and long-term mortality was recorded. Results: Mean admission serum chloride levels were 102±5 mEq/l. 97 out of 305 (37%) patients experienced incident hypochloremia. Patients with incident hypochloremia were older (78±10 vs 73±12 years, p=0.01), had lower admission LVEF (34±8% vs 37±8%, p=0.009), and longer hospital stay (9±4 vs 7±4 days, p=0.0003). During hospitalization patients with incident hypochloremia had higher rates of complication (45% vs 32%, p=0.01), lower levels of natremia and azotemia at admission and discharge. At long term follow-up incident hypochloremia was associated with increased risk of MACE (49% vs 32%, p=0.005) and death (42% vs 24%, p=0.002, log rank p<0.01). Conclusion: Incident hypochloremia is a common finding among hospitalized patients with TTS, associated with higher risk of in-hospital events and long-term MACE and death.